#### Probability

##### Junior Member

- Joined
- Jan 26, 2012

- Messages
- 195

OK tried this all night to solve and not getting anywhere.

- 1/3x + 13/3 = - 2x - 4

First method

12x/3 = - 2x - 4

4x = - 2x - 4

2x = - 4 (NO)

Second method

-1/3x + 13/3 = - 2x - 4

multiply through by 3

-3x + 13 = - 6x - 12

- 9x = 1 (NO)

Third method

-1/3x + 13/3 = -2x -4

-1x + 13 = -6x - 12

-7x = 1 (NO)

I should get x = -5

OK I think I have solved it?

- 1/3x + 13/3 = - 2x - 4

- x + 13 = - 6x - 12

x - x + 13 = - 6x + x - 12

13 = - 5x - 12

13 + 12 = - 5x - 12 + 12

25 = - 5x

x = - 5

- 1/3x + 13/3 = - 2x - 4

First method

12x/3 = - 2x - 4

4x = - 2x - 4

2x = - 4 (NO)

Second method

-1/3x + 13/3 = - 2x - 4

multiply through by 3

-3x + 13 = - 6x - 12

- 9x = 1 (NO)

Third method

-1/3x + 13/3 = -2x -4

-1x + 13 = -6x - 12

-7x = 1 (NO)

I should get x = -5

OK I think I have solved it?

- 1/3x + 13/3 = - 2x - 4

- x + 13 = - 6x - 12

x - x + 13 = - 6x + x - 12

13 = - 5x - 12

13 + 12 = - 5x - 12 + 12

25 = - 5x

x = - 5

Last edited: